The Effect of Radiation Dose on the Number of Leukocytes, Erythrocytes, and Thrombocytes in Cervical Cancer Patients Before and After Radiotherapy - Artitin, Cicillia; Nurmayana (Indonesian Journal Publisher, 2025)
This study aims to determine the effect of radiation on the number of leukocytes, erythrocytes, and thrombocytes in cervical cancer patients before and after radiotherapy. This study was conducted at the radiotherapy facility of Arifin Achmad Regional General Hospital in Pekanbaru using a quantitative research method with a retrospective approach and secondary data from the medical records of 18 stage IIB–IIIB cervical cancer patients who underwent total radiotherapy of 50 Gy in 25 fractions. Data analysis was performed using the paired sample t-test and Wilcoxon signed rank test. The results showed a decrease in the mean leukocyte count from 10,18×10³/µL to 6,81×10³/µL, erythrocyte count from 3,92×10⁶/µL to 3,55×10⁶/µL, and platelet count from 253,72×10³/ µL to 181,39×10³/µL. Statistical tests showed a significant difference (p<0.05) between before and after radiotherapy. It was concluded that linac radiation had a significant effect on the decrease in the number of leukocytes, erythrocytes, and platelets in cervical cancer patients, so routine blood monitoring during therapy was necessary to prevent hematological complications.